Prevalence of risk factors for obesity, hypertension, coronary artery disease and diabetes among under-graduate medical college students of Tamil Nadu - Ibrahim, Razeek Mohammed; Palaniyappan Priyadarsini, Sengoda Gounder; Nayeem, Rahim Abdul; Somasundaram, Vellomgattupalayam Muthusamy; Shankar, R. (International Journal Of Community Medicine And Public Health, 2017)
Background: The present scenario indicates that NCD-related diseases are on the rise among young people. Once the behavioural patterns of an individual are established, it often persists throughout life and is hard to change. Research has documented that adolescence is the appropriate time period for appropriate intervention. The aim of the study was toassess the prevalence of various risk factors of hypertension, coronary artery disease and diabetes among the medical students. Methods: A cross-sectional observational study was conducted among the medical college students of Annapoorna Medical College Hospital for a period of one year. A total of 406 students had participated in the study. A semi-structured and pilot tested questionnaire was used to collect the personal and demographic details of the students. Measurements such as BMI and blood pressure were recorded. Biochemical measurements such as fasting blood sugar and lipid parameters were measured. Results: A total of 38 (17.9%) male students and 6 (3%) female students are at risk of developing diabetes, hypertension or CAD at a very early age as per their clinical and biochemical reports. Conclusions: Promotion of supportive environment for strengthening student-based approaches and strategic delivery of health education is essential to target the risk behaviours among our future doctors.